2014
DOI: 10.1590/0037-8682-0245-2013
|View full text |Cite
|
Sign up to set email alerts
|

Proprioceptive neuromuscular facilitation in HTLV-I-associated myelopathy/tropical spastic paraparesis

Abstract: introduction: Human T cell lymphotropic virus type I-associated myelopathy/tropical spastic paraparesis (HAM/TSP) can impact the independence and motricity of patients. The aims of this study were to estimate the effects of physiotherapy on the functionality of patients with HAM/TSP during the stable phase of the disease using proprioceptive neuromuscular facilitation (PNF) and to compare two methods of treatment delivery. Methods: Fourteen patients with human T cell lymphotropic virus type I (HTLV-I) were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…Furthermore, the abnormal sensory input and motor neuron activity (15) were reduced more substantially when the PNF technique was utilized in this study. Therefore, strength exercises can reduce muscle spasticity and improve neural control while maintaining extensibility (13) , which was observed in the present study for the quadriceps muscles (Figure 1).…”
supporting
confidence: 70%
See 1 more Smart Citation
“…Furthermore, the abnormal sensory input and motor neuron activity (15) were reduced more substantially when the PNF technique was utilized in this study. Therefore, strength exercises can reduce muscle spasticity and improve neural control while maintaining extensibility (13) , which was observed in the present study for the quadriceps muscles (Figure 1).…”
supporting
confidence: 70%
“…Studies have shown that the ICF provides a scientifi c basis for understanding and studying health (10) (11) (12) . However, the ICF and Ashworth Scale are rarely used in HAM/ TSP patients (13) .…”
mentioning
confidence: 99%
“…4,20,21 The hip adductors, knee extensors and ankle plantar flexors were evaluated for the assessment of spasticity, which are the most commonly tested muscles for the evaluation of spasticity in the lower limbs. 11,[22][23][24] No significant difference in spasticity was found between the right and left legs (Table 1). Moreover, patients with HAM/TSP exhibited a slight increase in muscle tone (median score of 1+), although with variation.…”
Section: Resultsmentioning
confidence: 99%
“…Patterns were rolling supine to lateral, transition from sitting to standing, standing on one leg, weight shifting forward and backward, walking forwards, backwards and sideways, going up and down stairs 14 . The PNF improved muscle tone, low back pain, functional performance and gait speed 16 .…”
mentioning
confidence: 89%
“…Skin receptors were stimulated by manual contact on the cutaneous region related to the specific muscle or motion desired, joint approximation or traction, and diagonal and rotational movement patterns 14 . Passive and assisted phases of rhythmic initiation stimulated rolling, sitting and crawling 14,16 . Manual assistance was performed on a minimum of two muscles or muscle regions, with a minimum of five repetitions, in every session.…”
Section: Interventionmentioning
confidence: 99%